The Importance of Understanding Accounting Information Systems for the Internal Performance of Financial Auditors - Gunawan, Asep; Nurhawaeny, Endah; Suprihatin, Dina (Jurnal Ekuisci, 2024)
Technological advancements are a consequence of societal progress. Technology is continuously advancing to fulfill the ever-changing demands of humans, which includes accounting information systems. The objective of this study is to ascertain the significance of accounting information systems in relation to the internal performance of financial auditors within a firm. This study used a case study methodology to investigate and assess the impact of accounting information systems on the internal performance of auditors at the Cimanuk Cisanggarung Cirebon Center. This research is a form of quantitative descriptive research that aims to elucidate the degree to which accounting information systems impact the internal performance of auditors. The study findings indicate that having a comprehensive grasp of the accounting information system has a substantial impact on the internal performance of a financial auditor within a company.